Private Saving, Public Saving, and the Inflation Tax : Another Look At An Old Issue - Hamann, A. (IMF Working Papers; Working Paper ;, 1993)
The present paper provides an analytical discussion on a popular issue: the measurement problems associated with the inflation tax. It is well known that conventional national accounts definitions usually misplace the proceeds from the inflation tax: they are typically not subtracted from disposable income, and they are not included as part of the Government's revenues 'above the line.' Using a simple, perfect foresight monetary model developed by Calvo (1986, 1987), this paper analyzes the difference between macroeconomically relevant concepts of public and private saving, and their national accounts counterparts. The paper goes on to show that the national account aggregates create the impression that heavier reliance on the inflation tax on the part of the Government is associated with higher private saving, even in situations where the composition of government revenues does not have any effect on private saving.